Composition, structure and mechanical properties of metal oxide coatings produced on titanium using plasma spraying and modified by micro-arc oxidation. Issue 11 (1st August 2018) - Koshuro, Vladimir; Fomin, Aleksandr; Rodionov, Igor
Abstract: Metal oxide coatings on VT6 titanium alloy were formed by plasma spraying of aluminum oxide powder and subsequent microarc oxidation at a current density from 1 to 3 kA/m 2 . As a result of combined treatment, metal oxide coatings consisting of a mixture of aluminum and titanium oxides were obtained on the surface of titanium samples. The most pronounced changes in the morphology of the plasma-sprayed coating were observed at the highest current density of 3 kA/m 2 . The open porosity decreased from 56% to 38% due to the modification by micro-arc discharges, whereas the microhardness increased from 1013 ± 150 HV to 1639 ± 31 HV.